PENGARUH PEMBELAJARAN TEMATIK TERPADU MENGGUNAKAN DISCOVERY LEARNING TERHADAP PENGETAHUAN SISWA SEKOLAH DASAR TENTANG PENINGGALAN SEJARAH - Widi Winarni, Endang; Dadi, Sri; Lusa, Herman (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2017)
Abstract: The purpose of this research is to know the influence of Integrated Thematic Learning usingDiscovery Learning to the Knowledge of Elementary School Students about Historical Heritage. Theresearch design used was the matching only pretest-posttest control group design. The study population isall fourth grade students of elementary school in Bengkulu city of academic year 2017-2018. The sampleof the research is the fourth grader of Public Elementary School 68 as the experimental group that iscarrying out the learning with discovery learning by visiting the museum and IVA of the State ElementarySchool 05 Kota Bengkulu as the control group with the image media. The instrument used in this study isa test sheet to measure students' knowledge of historical relics. The data of the research were analyzedinferential statistically with t-test. The results showed that the mean score difference between posttest andpretest in the control group was 20.95 and in the experimental group was 39.66. The result of t calculationis 0,27 and t table 2,00. So it can be concluded there is no significant effect of thematic learning based onlocal culture with discovery learning to the knowledge of elementary students about the historical relics. Key word : Thematic learning, historical knowledge, discovery learning Abstrak :Tujuan penelitian ini untuk mengetahui pengaruh Pembelajaran Tematik Terpadu menggunakan Discovery Learning terhadap Pengetahuan siswa Sekolah Dasar tentang Peninggalan Sejarah. Desainpenelitian yang digunakan adalah the matching only pretest-posttest control group design. Populasipenelitian adalah seluruh siswa kelas IV Sekolah Dasar di kota Bengkulu tahun ajaran 2017-2018. Sampelpenelitian adalah siswa kelas IV Sekolah Dasar Negeri 68 sebagai keompok eksperimen yaitumelaksanakan pembelajaran dengan discovery learning dengan mengunjungi museum dan IVA SekolahDasar Negeri 05 Kota Bengkulu sebagai kelompok kontrol dengan media gambar. Instrumen yangdigunakan dalam penelitian ini adalah lembar tes untuk mengukur pengetahuan siswa tentang peninggalansejarah. Data hasil penelitian dianalisis secara statistik inferensial dengan uji-t. Hasil penelitian diketahuibahwa rata-rata selisih skor antara postest dan pretest pada kelompok kontrol sebesar 20,95 dan padakelompok eksperimen sebesar 39,66. Hasil analisis t hitung sebesar 0,27 dan t tabel 2,00. Sehingga dapatdisimpulkan tidak terdapat pengaruh yang signifikan pembelajaran tematik berbasis budaya lokal dengandiscovery learning terhadap pengetahuan siswa Sekolah Dasar tentang peninggalan sejarah Kata kunci: Pembelajaran tematik, pengetahuan peninggalan sejarah, discovery learning